Aberrant TGF‐β signaling underlies the pathogenesis of aortic aneurysm in Shprintzen‐Goldberg syndrome. (12th March 2013) - Jan, A
Abstract : Mutations in the TGF‐β repressor SKI cause Shprintzen‐Goldberg syndrome with aortic aneurysm Doyle et al. (2012) Nature Genetics 44(11):1249–54